An investigation of mineral distribution in coking and thermal coal chars as fuels for the direct carbon fuel cell. (1st April 2018) - Allen, Jessica A.; Glenn, Michael; Hapugoda, Priyanthi; Stanger, Rohan; O'Brien, Graham; Donne, Scott W.
Highlights: First time use of coal grain and mineral liberation analysis on coal chars. Identification of two different property sets in electrochemical carbon activation. Catalytic effect of kaolinite mineral shown to depend heavily on distribution. Mineral distribution shown to impact more on performance than carbon properties. Abstract: For the first time, a combination of coal grain analysis (CGA) and mineral liberation analysis (MLA) has been applied to coal chars prepared at different pyrolysis temperatures. Information collected from these powerful techniques is used here to assess electrochemical activity of coal chars in a solid anode of the direct carbon fuel cell. Mineral distribution and consideration of particle size gives very useful information in terms of showing differences between chars of differing origin, although major differences in mineral distribution between pyrolysis HHT are not observed here. As a result of this analysis, it is proposed that electrochemical performance of coal chars at solid anodes in molten carbonate appear to be dependent on several, interlinked factors. The physical properties of the char including its porosity, resistivity, surface area and crystalline structure have previously been demonstrated to affect electrochemical oxidation of carbons, and these factors are also observed to be important here. Further, however, the prevalence, size and type of mineral matter in the coal char and its contact with char particles also is suggested to play an equally important role. The mechanism of this interaction may include alteration of previously observed sensitivities, such as mineral enhanced gasification of the coal char leading to carbon morphology changes. Additional influences of mineral matter are suggested here to include modification of surface polarity and subsequent contact between carbon and molten carbonate electrolyte (effectively enhancing surface area), or the ability of mineral components to act as a shuttle for active species.